Review NOAM LUBELL, JELENA PEJIĆ, CLAIRE SIMMONS, GUIDELINES ON INVESTIGATING VIOLATIONS OF INTERNATIONAL HUMANITARIAN LAW: LAW, POLICY AND GOOD PRACTICE, THE GENEVA ACADEMY OF INTERNATIONAL HUMANITARIAN LAW AND HUMAN RIGHTS, INTERNATIONAL COMMITTEE OF THE RED C - Stojanović, Bojan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Guidelines on Investigating Violations of International Humanitarian Law: Law, Policy and Good Practice, authored by Noam Lubell, Jelena Pejić and Claire Simmons, published by the Geneva Academy of International Humanitarian Law and Human Rights and the International Committee of the Red Cross, is a valuable document in the form of 16 guidelines which are of great use in investigating and recording violations of IHL provisions. In addition to the 16 guidelines that accompany the comments, the Guidelines also contain a general introduction, four chapters, an explanation of the methodology, a list of sources and a list of experts consulted. The Guidelines explain the purpose of the Guidelines (legal and non-legal reasons) and thus explain the multiplicity of the need to draft such a document of great practical importance.